Sosialisasi Teknologi Pendidikan Berhitung Kreatif - Stephanus Goenawan; Stephen Aprius Sutresno; Trifenaus Prabu Hidayat (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
Learning mathematics, especially arithmetic and number patterns, is often a challenge for students due to the lack of creative approaches and the use of technology in the learning process. This community service program aims to improve the competence of teachers and lecturers in teaching innovative arithmetic concepts through the Educational Technology Online Workshop: Creative Arithmetic in the Era of Artificial Intelligence. This activity is conducted online and attended by participants from various backgrounds, including teachers, students, and the general public. The implementation method includes introducing the concept of regularity of number patterns, demonstrating the Vertical Metric method, and training in using web-based digital applications for creative calculations from licensed association partners. The activity results showed an increase in participants' understanding of developing creative learning strategies and high enthusiasm from participants in implementing technology-based arithmetic methods in their respective educational environments. This training positively impacts educators' pedagogical skills and encourages students' interest in learning mathematics through a more interesting and applicable approach.